rpl-11.1 Knockdown Disturbs Translation Machinery and Proteostasis in Caenorhabditis Elegans (Global Journal of Science Frontier Research, 2024)
An array of human chronic diseases, such as Alzheimer's disease, Huntington's disease, and Parkinson's disease, are related to defects in cellular proteostasis and the formation of protein aggregates. Using Caenorhabditis elegans PP563, a model organism developed for studying proteostasis stress, we can elucidate the biological role of specific genes and proteins involved in translation and proteostasis, advancing our understanding of relevant pathologies and therapeutics. Here, we report the knockdown of rpl-11.1 in C. elegans leads to disturbance in protein translation and proteostasis pathways, including the Ubiquitin-Proteosome System (UPS) and selective autophagy. We confirmed the importance of rpl-11.1 in ensuring correct ribosome biogenesis and translation accuracy.
Keywords: rpl-111; caenorhabditis elegans; RNAi; ubiquitin-proteosome system; selective autophagy; germline apoptosis